Economic use of waste Musa paradisica peels for effective control of mild steel loss in aggressive acid solutions - Tiwari P.; Srivastava M.; Mishra R.; Ji G.; Prakash R. (My University, 2025)
Cost effective prevention of steel corrosion utilizing eco-friendly materials is a high priority subject for the industries, these days. In this regard, we have explored ethyl acetate extract of Musa paradisica peels (EAEMPP) for mild steel protection in acidic media (hydrochloric and sulfuric acids). The electrostatic interaction of EAEMPP molecules with mild steel has been verified using UV-vis spectroscopy that clearly indicates extract molecules being adsorbed on the surface. The corrosion behavior of mild steel substrate in the presence of the fruit peel extract was investigated by Tafel polarization curves, linear polarization and electrochemical impedance spectroscopy (EIS) techniques. The results of electrochemical study strongly validate that EAEMPP limits the oxidation as well as reduction reactions at the active centers of the metal surface and thus retards mild steel corrosion in both acidic media. Variations in surface morphology of the mild steel with and without inhibitor have been studied via scanning electron microscopy (SEM) and atomic force microscopy (AFM), which has directly verified the reductions of corrosion loss. The adsorption behavior of the extract in both acid media is also studied, which is described suitably with Langmuir isotherm. Quantum chemical parameters, calculated by DFT calculations, have also aided in better understanding of the corrosion inhibition mechanism. We believe that employing green inhibitors from food waste may be useful in corrosion protection of mild steel with economical and ecological approach. © 2018 Elsevier Ltd. All rights reserved.